Metal artifact reduction by dual energy computed tomography using monoenergetic extrapolation - Bamberg, Fabian; Dierks, Alexander; Nikolaou, Konstantin; Reiser, Maximilian F.; Becker, Christoph R.; Johnson, Thorsten R. C. (European radiology, 2011)
Objective The aim of the study was to assess the performance and diagnostic value of a dual energy CT approach to reduce metal artefacts in subjects with metallic implants. Methods 31 patients were examined in the area of their metallic implants using a dual energy CT protocol (filtered 140 kVp and 100 kVp spectrum, tube current relation: 3:1). Specific post-processing was applied to generate energies of standard 120 and 140 kVp spectra as well as a filtered 140 kVp spectrum with mean photon energies of 64, 69 and 88 keV, respectively, and an optimized hard spectrum of 95–150 keV. Image quality and diagnostic value were subjectively and objectively determined. Results Image quality was rated superior to the standard image in 29/31 high energy reconstructions; the diagnostic value was rated superior in 27 patients. Image quality and diagnostic value scores improved significantly from 3.5 to 2.1 and from 3.6 to 1.9, respectively. In several exams decisive diagnostic features were only discernible in the high energy reconstructions. The density of the artefacts decreased from −882 to −341 HU. Conclusions Dual Energy CT with specific postprocessing can reduce metal artefacts and may significantly enhance diagnostic value in the evaluation of metallic implants.